2022
DOI: 10.1007/s10863-022-09940-9
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 inhibitor alleviates sepsis-induced organ failure by inhibiting platelet mtROS production, autophagy, and GPIIb/IIIa expression

Abstract: Thrombocytopenia and impaired platelet aggregation are associated with sepsis-induced organ failure.Many studies have shown that mitochondrial ROS, autophagy is related to organ injury in sepsis. However, the relationship between them is unknown. Here, we explored whether Toll Like Receptor 4 inhibitor alleviates sepsis organ failure by inhibiting platelet mitochondrial ROS production, autophagy, and GPIIb/IIIa expression. We found Toll Like Receptor 4 inhibitor TAK242 alleviated LPS-induced acute kidney and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The following information was noted, including the first author of the included studies, year of publication, experimental model or participant, methods for establishing sepsis-induced AKI, the status of autophagy, associated genes or pathways in the action of autophagy, and the main findings of the relevant studies. Finally, there were 41 experimental and clinical studies (7, 14-33) (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53) included in the review. The selection process for screening the relevant studies shown in Supplementary Figure 1.…”
Section: A Search Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The following information was noted, including the first author of the included studies, year of publication, experimental model or participant, methods for establishing sepsis-induced AKI, the status of autophagy, associated genes or pathways in the action of autophagy, and the main findings of the relevant studies. Finally, there were 41 experimental and clinical studies (7, 14-33) (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53) included in the review. The selection process for screening the relevant studies shown in Supplementary Figure 1.…”
Section: A Search Of the Literaturementioning
confidence: 99%
“…LPS-induced platelet autophagy by generating mitochondrial ROS. Li et al (36) showed that TLR4 inhibitor TAK242 might effectively alleviate SI-AKI by inhibiting platelet GPIIb/IIIa and platelet activation. Ulinastatin, a urinary trypsin inhibitor, functions to control a series of proinflammatory mediators and cytokines.…”
Section: Other Potential Mechanismsmentioning
confidence: 99%
“…LPS triggers a cascade of intracellular signaling pathways through the TLR4/MD2 receptor complex, resulting in the activation of the proinflammatory transcription factor NF-κB and the production of inflammatory mediators, including NO, TNF-α, and IL-12. , In addition, LPS-induced depolarization of mitochondrial membrane potential and the resulting increase in mtROS production contribute to organ injury in endotoxemia. ,, Therefore, inhibiting NF-κB and mtROS has been identified as a promising therapeutic strategy for treating LPS-induced inflammatory disorders, including endotoxemia . Recent studies have identified phytochemicals and molecules that target the TLR4/MD2 receptor complex and prevent endotoxemia in experimental models with efficient safety and pharmacokinetics in preclinical and clinical trials. , Previously, Lee et al reported that 3′,4′-dihydroxyflavone (DHF) binds with MD2 and disrupts LPS binding with TLR4/MD2 receptor complex and inhibit the inflammatory response by downregulating the NF-κB signaling pathway and ROS production in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 In addition, LPS-induced depolarization of mitochondrial membrane potential and the resulting increase in mtROS production contribute to organ injury in endotoxemia. 14,15,44 Therefore, inhibiting NF-κB and mtROS has been identified as a promising therapeutic strategy for treating LPS-induced inflammatory disorders, including endotoxemia. 45 Recent studies have identified phytochemicals and molecules that target the TLR4/MD2 receptor complex and prevent endotoxemia in experimental models with efficient safety and pharmacokinetics in preclinical and clinical trials.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Previous studies have shown that TLR4 is activated after LPS stimulation and regulates autophagy via the TLR4-myeloid differentiation primary response 88 (MyD88)-mitogen-activated protein kinase (MAPK)/NF-κB and TLR4/Phosphoinositide 3-kinase (PI3K)/v-akt murine thymoma viral oncogene homologue (Akt)/mTOR signaling pathways ( Kawai and Akira, 2011 ; Monlish et al, 2016 ). A recent study demonstrated that inhibition of TLR4 by resatrovid (TAK242) mitigated sepsis-induced kidney injury through inhibiting autophagy ( Li and Feng, 2022 ). Another study isolated renal TECs from C57Bl/10ScN mice without functional TLR4 and incubated them with LPS.…”
Section: Autophagy In Sepsis-induced Acute Kidney Injurymentioning
confidence: 99%